Development and in vitro evaluation of a buccoadhesive pindolol tablet formulation - (:unkn) unknown (MARCEL DEKKER INC, 1998)
Controlled-release buccoadhesive tablets containing pindolol were prepared and evaluated in order to achieve constant plasma concentrations during the treatment of chronic hypertension and to improve the bioavailability of pindolol by the avoidance of hepatic first-pass metabolism. The formulations were tested for weight, hardness, friability, content uniformity, swelling rate, bioadhesive force, and drug release rate values. Carbopol 934 and NaCMC were used as bioadhesive polymers and Methocel K4M, Methocel K15M, and HPC were added as matrix-forming polymers.
Keywords: CONTROLLED-RELEASE SYSTEMS; BIOADHESIVE ANALYSIS; METHYLCELLULOSE; MICROPARTICLES; HYDROGELS; POLYMERS